Emily's big shot - Avery, Bryan Patrick (Avery, Bryan Patrick. Mr. Grizley's class., 2022)
Emily has trouble simultaneously managing her wheelchair and passing the ball in her class's games of floor hockey, so classmates Dmitry and Ryan offer to help her improve--first lesson is learn to relax and not get nervous. Includes a special activity reinforcing social emotional learning skills.